2022
DOI: 10.1136/ijgc-2021-003165
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin plus paclitaxel and bevacizumab versus carboplatin plus paclitaxel and bevacizumab for the first-line treatment of metastatic or recurrent cervical cancer

Abstract: ObjectiveCisplatin-paclitaxel and bevacizumab is a frequently used treatment regimen for metastatic or recurrent cervical cancer, and carboplatin-paclitaxel and bevacizumab are also among the recommended regimens. In this study we aimed to evaluate the efficacy of these two regimens for the treatment of metastatic or recurrent cervical cancer.MethodsPatients with metastatic or recurrent cervical cancer treated with cisplatin-paclitaxel and bevacizumab or carboplatin-paclitaxel and bevacizumab were retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In the CECILIA study [ 16 ], 57% of the patients received bevacizumab maintenance therapy for up to 53 courses. In a recent report, 18.5% of the TP plus bevacizumab group and 21.1% of the TC plus bevacizumab group received at least one or more courses of bevacizumab maintenance therapy, and the median (range) number of maintenance courses was 8 (2–24) and 9 (1–56), respectively [ 17 ]. As mentioned above, the number of bevacizumab maintenance courses currently varies and depends on the discretion of the attending physician.…”
Section: Discussionmentioning
confidence: 99%
“…In the CECILIA study [ 16 ], 57% of the patients received bevacizumab maintenance therapy for up to 53 courses. In a recent report, 18.5% of the TP plus bevacizumab group and 21.1% of the TC plus bevacizumab group received at least one or more courses of bevacizumab maintenance therapy, and the median (range) number of maintenance courses was 8 (2–24) and 9 (1–56), respectively [ 17 ]. As mentioned above, the number of bevacizumab maintenance courses currently varies and depends on the discretion of the attending physician.…”
Section: Discussionmentioning
confidence: 99%
“…Platinum–paclitaxel in combination with bevacizumab has been established as the standard treatment regimen for R/M CC, yielding an ORR of 55.8% to 64.5% and mPFS ranging from 9.2 to 10.8 months, and an mOS ranging from 16.4 to 19.1 months ( 26, 27 ). However, in patients who received platinum–paclitaxel regimens without bevacizumab, ORR ranged from 58.8% to 62.6% and mPFS ranged from 4.8 to 7.9 months in the JCOG0505 study, and mOS was 9.7 in the GOG-169 study and 13.3 months in the GOG-240 study, as previously reported ( 6, 28, 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, both cisplatin- and carboplatin-based treatments were used in neoadjuvant cervical cancer studies. It is known that objective responses are higher with cisplatin-based treatments [ 21 ]. Therefore, in the present study, cisplatin was specifically preferred for its high response rates.…”
Section: Discussionmentioning
confidence: 99%